RECOMMENDER SYSTEMS: A FOCUS FROM THE GENETIC ALGORITHMS - Velez-Langs, Oswaldo (2006)
This work presents an alternative approach (Evolutionary Algorithms approach) to traditional treatment of Recommender Systems (RSs). The work examines genetic algorithms possibilities to offer adaptive characteristics to this systems trough learning. The main goal, in addition to give a general view about RSs capabilities and possibilities, it is to provide an example mechanism for to extend RSs learning capabilities (from users´s personal chracteristics), with the purpose to improve the effectiveness in the moment of to find recommendations and appropriate suggestions for particular individuals.